Design and simulation load flow of grid - connected PV system on distribution network Using ETAP software Application Ain ELmelh /Msila PV station - SAADA, Adel; Enca/ Salim, DJERIOU (University of M'sila, 2022)
Nowadays, the integration PV system on distribution network is getting popular because of its advantage of renewable integration to the traditional power grid.in this project, a design of 20MW of micro grid system under different operating conditions to connect a distribution network are presented. the model of PV plants, inverters, cables, power transformer and 60KV transmission line was modeled using ETAP softwere. The load flow of all system starts with a PV module to consumers is studied and the parameters of Ain Elmelh PV station has used to approved all results. The simulation results have practical significance for real engineering.
Keywords: photoelectric, solar irradiation, photovoltaic power plants, Power grid, Electrical Transient Analyzer Program, Load Flow, transformer substation, power flow, short circuit analysis, harmonic analysis.